Hydrogen sulfide is an endogenous stimulator of angiogenesis - Papapetropoulos, Andreas (National Academy of Sciences, 2009)
The goal of the current study was to investigate the role of exogenous and endogenous hydrogen sulfide (H(2)S) on neovascularization and wound healing in vitro and in vivo. Incubation of endothelial cells (ECs) with H(2)S enhanced their angiogenic potential, evidenced by accelerated cell growth, migration, and capillary morphogenesis on Matrigel. Treatment of chicken chorioallantoic membranes (CAMS) with H(2)S increased vascular length. Exposure of ECs to H(2)S resulted in increased phosphorylation of Akt, ERK, and p38. The K(ATP) channel blocker glibenclamide or the p38 inhibitor SB203580 abolished H(2)S-induced EC motility. Since glibenclamide inhibited H(2)S-triggered p38 phosphorylation, we propose that K(ATP) channels lay upstream of p38 in this process. When CAMs were treated with H(2)S biosynthesis inhibitors dl-propylargylglycine or beta-cyano-L-alanine, a reduction in vessel length and branching was observed, indicating that H(2)S serves as an endogenous stimulator of the angiogenic response. Stimulation of ECs with vascular endothelial growth factor (VEGF) increased H(2)S release, while pharmacological inhibition of H(2)S production or K(ATP) channels or silencing of cystathionine gamma-lyase (CSE) attenuated VEGF signaling and migration of ECs. These results implicate endothelial H(2)S synthesis in the pro-angiogenic action of VEGF. Aortic rings isolated from CSE knockout mice exhibited markedly reduced microvessel formation in response to VEGF when compared to wild-type littermates. Finally, in vivo, topical administration of H(2)S enhanced wound healing in a rat model, while wound healing was delayed in CSE(−/−) mice. We conclude that endogenous and exogenous H(2)S stimulates EC-related angiogenic properties through a K(ATP) channel/MAPK pathway.